Agama, Dogma, dan Kebenaran; Kritik Rasionalitas Ibn Thufail dalam Karya Hayy Ibn Yaqdzon dan Falsifikasi Popper - Salim, Achmad Ilham Attamimi; Aminim, Muhammad Ibnu; Maria, Galuh (JOM, 2025)
This article examines Ibn Thufail's rationality critique of religious dogma and the concept of truth, and relates it to Karl Popper's theory of falsification. This research uses philosophical and comparative analysis methods to understand the relationship between rationality, religion, and truth. The results show that Ibn Thufail's criticism in his work Hayy Ibn Yaqdzon against religious dogma is still relevant and can be strengthened by Popper's falsification theory. The author discusses Hayy Ibn Yaqdzon's concept of rationality and Popper's falsification theory in ‘The Logic of Scientific Discovery’. A comparative analysis showed the similarities between criticism of religious dogma and criticism of scientific dogma through Popper's falsification theory. Both emphasise the importance of critical thinking and rationality in understanding truth. The results of this study contribute to a deeper understanding of the relationship between rationality, religion and truth. This article also opens a discourse on the relevance of classical Islamic philosophers' thoughts in the modern context.